Answer:
(f - g)(2) = 2
Step-by-step explanation:
Given the functions below, find (f - g) (2).
f(x) = x² + 3
g(x) = 4x – 3
(f - g)(x) = (x²+3)-(4x-3)
(f - g)(x) = x²+3-4x+3
(f - g)(x) = x²-4x+6
(f - g)(2) = (2)²-4(2)+6
(f - g)(2) = 4-8+6
(f - g)(2) = 2
The answer to that question is 38.
The first numerator is 3 and the second is 17 not 2
<span>We can, transform the raw scores to z-scores and use the standard normal curve to find the relative frequency of the scores.
I hope this helped!</span>
Answer:
b=23 degrees
Step-by-step explanation:
a was 66 degrees so b=23 degrees 180-90-66=23